Inquiry in project-based science classrooms: Initial attempts by middle school students - Krajcik, Joseph S.; Blumenfeld, Phyllis C.; Marx, Ronald W.; Bass, Kristin M.; Fredericks, Jennifer; Soloway, Elliot (The journal of the learning sciences, 1998)
Although inquiry is an essential component of science learning, we know little about students' experience with inquiry in regular science classrooms. Our goal is to describe realistically what middle school students do and where they have difficulties in their first encounters with inquiry learning. We report findings from case studies of 8 students as they designed and carried out their own investigations during 2 projects that spanned several months. We detail how students asked questions, planned and designed investigations and procedures, constructed apparatus, carried out their work, interpreted data and drew conclusions, and presented the findings. We discuss how collaboration among group members and support from the teacher influenced this process. The findings indicate that middle school students were thoughtful in designing investigations and in planning procedures; for instance, they thought about controls, about samples, and about how to organize data collection. However, the cases also reveal areas of weakness, such as failures to focus on the scientific merit of questions generated and to systematically collect and analyze data and draw conclusions. Teacher structuring and questioning were crucial in encouraging students to be thoughtful about the substantive aspects of inquiry. Overall, these findings can help curriculum developers and science educators in their attempts to design instruction to improve the inquiry process.
Keywords: apprentissage par projet; enseignement secondaire; innovation pédagogique; sciences